2018
DOI: 10.3390/ijerph15081567
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from Food Consumption Score to Cardiovascular Disease: A Seven-Year Follow-Up Study of Indonesian Adults

Abstract: Background: Available prospective studies of food insecurity and cardiovascular diseases (CVD) have included obesity and hypertension as the modifiable risk factors. Studies using the physical activity measures are lacking, and where to contribute to counterbalance the risk associated with food insecurity and CVD remains unclear. We aimed to use structural equation modelling (SEM) to explore the complex direct and indirect factor variables influencing cardiovascular disease (CVD) during a seven-year follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…The sum of the score for the food groups is the FCS. FCS has been validated to be used in developing countries such as Indonesia, and it has been widely used by previous studies to measure the household food security status in this country, such as Hasanah, et al [45]; Isaura, et al [46]; Toiba, et al [47].…”
Section: Measuring Income and Food Securitymentioning
confidence: 99%
“…The sum of the score for the food groups is the FCS. FCS has been validated to be used in developing countries such as Indonesia, and it has been widely used by previous studies to measure the household food security status in this country, such as Hasanah, et al [45]; Isaura, et al [46]; Toiba, et al [47].…”
Section: Measuring Income and Food Securitymentioning
confidence: 99%
“…(6,13). While the main modifiable risk factors include smoking, alcohol consumption, lifestyle, obesity and nutrition (14,15). Other factors that has also been showed to cause NCDs include mental problems (depression, anxiety), adolescent delinquency, as well as sedentary lifestyle and poor diet (16).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, people with food insecurity may encounter sleep disturbance, which is also associated with an increase in systolic blood pressure. The systolic blood pressure may be a result of jobs involving heavy work or of continuous vigorous physical activity [58][59][60]. A population-based study in a rural area of China found that older age, unemployment, lower-income, disability, and chronic disease comorbidities were significant factors associated with an increased risk of poor sleep quality for both men and women [61].…”
Section: Discussionmentioning
confidence: 99%